AN EFFECT OF BENZIHOL ON RICE PRODUCTIVITY - P. I. Kostylev; N. V. Repkina; Yu. P. Kalievskaya (Зерновое хозяйство России)
The article deals with the use of growth regulator ‘benzihol’ to increase rice productivity. It is a structural analogue of the well-known retardant ‘chlorine choline chloride’ (Cholini chloridum). The medicine is a phyto regulator of new generation, which possesses auxin, retardant, stress protective and immune-modulating activity. The seeds of the variety ‘Kuboyar’ were treated with the medicine before sowing (5 mg/t) and the leaves of vegetating plants were treated with it in the period of tillering (5 mg/ha). The variants of the trial are a control, treatment of seeds, treatment of leaves, treatment of seeds and leaves. The ancestors are a vast layer of perennial grasses (alfalfa), overturning of the layer, an ameliorative field and 2-d year of rice after an ameliorative field.  The study showed that rice productivity greatly increased with seeds and leaves treatment, which was recommended in the production. The seeds and leaves of the new variety ‘Kuboyar’ were treated with ‘benzihol’ and sown after alfalfa it formed the largest productivity during 4 years on average (8,57 t/ha, which was on 1,44 t/ha more than a control (7,13 t/ha). The other ancestors gave similar results.  On average grain productivity increased from 4,88 t/ha to 5,88 t/ha with treated seeds, 5,44 t/ha with treated leaves and 6,16 t/ha with dual treatment. The increases were 1,00 t/ha (20,4%), 0,56 t/ha (11,5%), 1,28 t/ha (26,2%) respectively. in the production it is recommended to use treatment of seeds, as less expensive.